(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The article covers the theoretical and practical aspects of the methodology of teaching the folk crafts technology section in technology lessons of secondary schools. The main types of Uzbek folk crafts, effective methods of teaching them to students, and ways of organizing lessons based on modern pedagogical technologies are analyzed. The authors also developed methodological recommendations for organizing practical classes and using interactive methods